INCREASING THE EFFICIENCY OF PHYSICAL EDUCATION OF STUDENTS IN HIGHER EDUCATION INSTITUTIONS - Sharipov Khabibullo Abdukakhorovich (Proximus Journal Publishing, 2024)
The article analyzes the current state of physical education of students in higher educational institutions. The main contradictions of the current system of physical education in higher educational institutions are outlined. The realities of physical education of students, the main trends of its modern development are revealed and the main ways to increase its effectiveness are proposed
Keywords: physical education; students; higher education institution